Analisis Kepatuhan Hukum UMKM Bakery Socah terhadap Kewajiban Sertifikasi Halal Perspektif Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal - Nur Husnul Khotimah; Hammam Hammam (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2025)
This study aims to determine the legal compliance of bakery MSMEs in Socah Village with the obligation of halal certification from the perspective of Law Number 33 of 2014 concerning Halal Product Assurance and to determine the obstacles of Socah bakery MSMEs in fulfilling halal certification obligations. This study is a descriptive qualitative type with an empirical legal approach. The primary data source used is an interview with bakery MSME owners in Socah Village. While secondary data sources are obtained from several other literatures that discuss the obligation of halal certification against Law Number 33 of 2014 concerning Halal Product Assurance. The results of this study are: 1) According to Article 4 of Law Number 33 of 2014, out of four bakery MSME actors, 2 MSME actors do not comply with the obligation of halal certification and 2 bakery MSMEs comply with the obligation of halal certification, namely V-vie bakery and Dapur Maryam. 2) the obstacles of business actors are the lack of knowledge and understanding of related business actors and the complicated halal certification process and also no support from the government. Keywords: Legal Compliance, UMKM, Bakery, Halal Certification.